IMPLEMENTATION OF ADAPTIVE METHODS IN LEARNING MANAGEMENT SYSTEMS - fadila, Dewi nurul; Susanto , Adi; Azise , Nur (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
Technological progress greatly affects all fields, one of which is the field of Education. Education in technology has become an important aspect of the modern world of Education. this research will discuss developing an adaptive e-learning application based on LMS. The app is designed to provide a learning experience that adapts to the individual needs of the learners. The method used in this study is the type of research development using Agile methods. The results of this research show that the use of adaptive e-learning applications based on LMS can increase the effectiveness of learning and provide motivation for students to get better results. Education can become more inclusive, dynamic, and adaptive with the use of e-learning applications such as these that can make it possible to support student development more innovatively and efficiently.